Legal Aspects of Breast Milk Donation in Indonesia - Syarifah, Mustika Chasanatusy; Lisnawati, Diana Arum; Hidayatih, Nurul (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Breast milk is the ideal source of nutrition for infants, supporting optimal growth and development. Beyond its nutritional value, breast milk plays a crucial role in strengthening infants' immunity and fostering emotional bonds between mother and child. Breast milk donation provides an alternative for infants who cannot receive exclusive breastfeeding from their mothers. This study analyzes the importance of breast milk donation, the legal framework governing the practice, and its perspective in Islamic law. This study uses a normative legal research method by conducting searches of regulations and literature related to the problems. The results of this study state that breast milk donation is important for babies who cannot get exclusive breast milk from their mothers for many reasons. Regulations on breast milk donation have been regulated in Indonesian law and are also permitted in Islamic law with proper recording